2011
DOI: 10.1309/ajcpuz53xzwqfyis
|View full text |Cite
|
Sign up to set email alerts
|

Meeting Regulatory Requirements by the Use of Cell Phone Text Message Notification With Autoescalation and Loop Closure for Reporting of Critical Laboratory Results

Abstract: Critical laboratory results require timely and accurate transmission to the appropriate caregiver to provide intervention to prevent an adverse outcome. We report the use of text messages to notify critical laboratory results in a large teaching hospital to manage the documentation and audit requirements of critical result reporting by regulatory agencies. The text messaging system (critical reportable result health care messaging system [CRR-HMS]) allows a receiver to acknowledge or reject a critical result b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…The interventions are described in Multimedia Appendices 8 and 9. Interventions using mobile communication technologies in both developed countries (Italy [205], US [1,92,206-228], UK [229-232], France [233], Canada [234-237], Japan [238], Australia [239], New Zealand [240], South Korea [241-245], and Denmark [246]), and developing ones (Thailand [247], Peru [248], Kenya [57,249,250], Taiwan [251,252], Israel [253-255], Uganda [256,257], Thailand [258], Singapore [259], Turkey [260], India [261], and South Africa [262]) have investigated the use of mobile phone-based apps, mobile phone voice call, SMS, and PDAs.…”
Section: Resultsmentioning
confidence: 99%
“…The interventions are described in Multimedia Appendices 8 and 9. Interventions using mobile communication technologies in both developed countries (Italy [205], US [1,92,206-228], UK [229-232], France [233], Canada [234-237], Japan [238], Australia [239], New Zealand [240], South Korea [241-245], and Denmark [246]), and developing ones (Thailand [247], Peru [248], Kenya [57,249,250], Taiwan [251,252], Israel [253-255], Uganda [256,257], Thailand [258], Singapore [259], Turkey [260], India [261], and South Africa [262]) have investigated the use of mobile phone-based apps, mobile phone voice call, SMS, and PDAs.…”
Section: Resultsmentioning
confidence: 99%
“…Embracing the use of smartphones therefore may have the potential to improve patient safety through strengthening the provision of easy access and trusted online resources, which have been shown to save time in performing clinical activities, as well as increasing adherence to hospital-specific protocols 14. In addition, the ability to remotely and securely access hospital applications and electronic records may provide a secure and efficient way to capture and upload relevant clinical images,15 and also aid in the development of innovative methods that allow the rapid communication of critical results to targeted physicians, facilitating rapid and timely interventions that may improve patient safety 16…”
Section: Discussionmentioning
confidence: 99%
“…Of the five studies identified that reported results about the change in communication of critical values after implementing an automated notification system, one [19] was excluded due to multiple sources of bias in how the reported estimate was measured prior to and following implementation of the practice. Each of the four remaining studies examined the effectiveness of automated notification systems using slightly different outcome measures, and each reported a substantial reduction in the time to communicate critical values.…”
Section: Evidence Of Automated Notification Practice Effectivenessmentioning
confidence: 99%
“…The electronic audit trail captured by the automated notification system can play an important role in performance monitoring and evaluation, including targeted interventions for clinicians who do not attend to critical results [19]. In addition, some observers have noted that the development of automated notification systems can productively lead to a reexamination of critical value policies and thresholds and the development of interpretative reporting support, particularly for critical results in areas such as coagulation disorders; hemoglobin and anemia evaluations; autoimmune disorders; serum protein analysis; immunophenotyping analysis; genetic and molecular diagnostics; endocrinology; toxicology; and other new tests with which clinicians may be less familiar [13].…”
Section: Additional Benefitsmentioning
confidence: 99%